Answer:
Step-by-step explanation:
The center of the circle is the midpoint of the two end points of the diameter.
Formula
Center = (x2 + x1)/2 , (y2 + y1)/2
Givens
x2 = 4
x1 = - 10
y2 = 6
y1 = - 2
Solution
Center = (4 - 10)/2, (6 - 2)/2
Center = -6/2 , 4/2
Center = - 3 , 2
So far what you have is
(x+3)^2 + (y - 2)^2 = r^2
Now you have to find the radius.
You can use either of the endpoints to find the radius.
find the distance from (4,6) to (-3,2)
r^2 = ( (x2 - x1)^2 + (y2 - y1)^2 )
x2 = 4
x1 = -3
y2 = 6
y1 = 2
r^2 = ( (4 - -3)^2 + (6 - 2)^2 )
r^2 = ( (7)^2 + 4^2)
r^2 = ( 49 + 16)
r^2 = 65
Ultimate formula is
(x+3)^2 + (y - 2)^2 = 65
The radius is √65 = 8.06
Answer:
Mean is 18
Step-by-step explanation:
We would set up the proportion as X/9=36/X so after we cross multiply we get x^2=324. Then we find the square root of both sides to simplify. ... And the square root of 324 is 18. So the final answer is x=18 or the geometric mean is 18
Answer:
it affected more than half
Step-by-step explanation:
Answer: 38.25
Step-by-step explanation: You divide the whole number by the denominator in the fraction.
153/4 = 38.25